Transcending the Culture–Nature Divide in Cultural Heritage - Sally Brockwell, Sue OʹConnor, and Denis Byrne (ANU E Press, 2013)
This volume began life as a session at the 2010 Australian Archaeological Conference on the cultural heritage of protected areas in the Asia-Pacific region. Our particular concern was with the proposition that the discourse of nature conservation was predisposed to a vision of protected areas (in the form of national parks and other ‘nature’ reserves) as pristine nature. According to such a vision, protected areas represent wildernesses that, having escaped the ravages of human exploitation, had now to be preserved as the last reservoirs of biodiversity on a planet threatened with ecological disaster. To what extent, we asked, did such a mindset eclipse the history and heritage of protected areas as human habitats, not to mention effacing the contemporary presence in them of living human cultures? These questions engage the much larger issue of the culture-nature divide as an ontological marker of Western modernity. This divide should more properly be described as a ‘duality’ or a ‘dyad’, terms that have been used to describe a habit of thought which developed in the West from the seventeenth century but with older antecedents. This habit of thought also produced the distinctive mind/body split which is particularly identified with the Cartesian worldview. In recent years there has been increasing interest in the real world ramifications of the culturenature duality from those working in fields ranging from sociology (for example, Latour 1993) and anthropology (Ingold 2000; Haraway 2006), to geography (Whatmore 2006; Head 2007). In Australia it has occupied the attention of Debbie Rose (1996, 2011) and others in the Ecological Humanities group.1 There has been a growing consciousness of the extent to which culture-nature dualism is foundational to Western modernity and thus seminal to the West’s encounter with the non-Western world. In modern Western thought, society (or culture) has been understood to be not just radically separate from nature but situated in a hierarchical relationship of dominance to it. This ontological model facilitated the vastly accelerated exploitation and despoliation of natural ‘resources’ (nature being considered a resource for humanity) which accompanied the Industrial Revolution, the development of capitalism and the European colonial-imperial project. Closer to home in terms of the present volume, culture-nature dualism has been found to be a major impediment to breaking out of the silos represented by nature conservation and heritage conservation. This, of course, is the view from the position of the experts. The view from the ground includes that of Indigenous people who find that in the struggle to maintain their land there are willing allies to be found among environmental and heritage conservation organisations but that these alliances mean having to internalise the culture-nature dichotomy, at least for the purposes of dealing with these experts, accessing their funding, and participating in their conservation programs. In other words such alliances entail an internalisation of an alien ontology.